Medical care usage and self-rated mental health - Rohrer James E (BMC, 2004)
Abstract Background Population studies frequently employ a single item dependent variable for overall health. Self-rated mental health has been the focus of attention less often. The purpose of this project was to investigate the relationship between use of medical care and poor mental health in an elderly population. Methods This study involved a cross-sectional telephone survey of persons over 65 years of age in West Texas, a sparsely-populated 108-county region. Independent variables included number of medical visits, race/ethnicity, age, gender and ability to pay for care. Mental health was measured by asking subjects how often they felt downhearted or blue. Results Multiple logistic regression analysis revealed that more medical visits were made by persons who were downhearted or blue. Females, persons who had difficulty paying for care, Hispanic respondents, and older persons were more likely to report poor mental health. Conclusions Elderly persons in this region who use more medical care are at greater risk of being in poor mental health. Public health agencies that are planning population-based approaches to improving mental health should consider targeting persons who are high users of medical care as well as those of limited means, women, persons of Hispanic ethnicity, and people who are of greater age.